5G nomadic deployment proposal of base station integrated with cloud and service - Furong XU; Hang CUI; Tianyi YU; Long ZHANG; Jinxia CHENG; Feng XING; Wuneng GUAN; Jing LIU; Wei DENG; Haiyu DING (Dianxin kexue)
Emergency scenarios such as floods, mobile scenarios such as open-pit mines, temporary coverage scenarios such as touring competitions have agile 5G network deployment and flexible local application deployment requirements.Existing solutions, such as emergency communication vehicles, drone communications, have three major problems, including inflexible backhaul, unsatisfied service, and incomplete scenarios.In response to the above-mentioned scenario requirements and problems, an innovative nomadic deployment proposal of base station integrated with cloud and service was proposed.It contained smart-simplified wireless coverage unit, smart-simplified backhaul unit, smart-simplified computing unit, and smart-simplified supporting unit.Smart-simplified wireless coverage unit and smart-simplified backhaul unit builded a ubiquitous network.Where there was demand, there was 5G.Smart-simplified computing unit builded a ubiquitous cloud.Where there was base station, there was cloud.Smart-simplified supporting unit realized the flexible movement of 5G network.The 5G nomadic base station integrated cloud and service to achieve flexible mobile 5G network and cloud, which could meet the needs of emergency rescue scenarios, mobile scenarios, and temporary industrial coverage scenarios.